CCT244747 is a novel, potent and selective CHK1 inhibitor with oral efficacy alone and in combination with genotoxic anticancer drugs - Walton, Mike I (2012)
PURPOSE: Many tumors exhibit defective cell cycle checkpoint control and increased replicative stress. CHK1 is critically involved in the DNA damage response and maintenance of replication fork stability. We have therefore discovered a novel, potent, highly selective, orally active, ATP competitive CHK1 inhibitor, CCT244747, and present its preclinical pharmacology and therapeutic activity. EXPERIMENTAL DESIGN: Cellular CHK1 activity was assessed using an ELISA assay and cytotoxicity a SRB assay. Biomarker modulation was measured using immunoblotting and cell cycle effects by flow cytometry. Single agent, oral CCT244747 antitumor activity was evaluated in a MYCN-driven transgenic mouse model of neuroblastoma by MRI and in genotoxic combinations in human tumor xenografts by growth delay. RESULTS: CCT244747 inhibited cellular CHK1 activity (IC(50) 29-170nM), significantly enhanced the cytotoxicity of several anticancer drugs and abrogated drug-induced S and G2 arrest in multiple tumor cell lines. Biomarkers of CHK1 (pS296 CHK1) activity and cell cycle inactivity (pY15 CDK1) were induced by genotoxics and inhibited by CCT244747 both in vitro and in vivo, producing enhanced DNA damage and apoptosis. Active tumor concentrations of CCT244747 were obtained following oral administration. The antitumor activity of both gemcitabine and irinotecan were significantly enhanced by CCT244747 in several human tumor xenografts, giving concomitant biomarker modulation indicative of CHK1 inhibition. CCT244747 also showed marked antitumor activity as a single agent in a MYCN-driven neuroblastoma. CONCLUSION: CCT244747 represents the first structural disclosure of a highly selective, orally active CHK1 inhibitor and warrants further evaluation alone or combined with genotoxic anticancer therapies.